Informative frequency band selection for performing envelope analysis under fluctuating operating conditions in the presence of strong noise and deterministic components - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2020)
Dissertation (MEng)--University of Pretoria, 2019.